An Agent Program Capable of Applying Local Search Strategies in the State Space of Well Defined Problems - França, Thayanne; F. Junior, Raimundo J. C.; Pereira, Jherson H. A.; Silveira, Francisca R. de V.; de Campos, Lidio M. L.; Araújo, Thelmo P.; de Campos, Gustavo A. L. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2018.4432, 2018)
Classical models of agents for solving well-defined problems are widely used in the literature but are limited to systematic search strategies in order to find the solutions. However, these strategies are not suited for all types of application. This work presents an adaption of classical models of agents for local search strategies. One agent system for neural network automatic design is used to show the feasibility of the proposal. The results are promising, since the model found satisfactory solutions for the proposed problems.